Analysis of Subsisdy Withdrawl on Fertilizers: - (Journal of Advances and Scholarly Researches in Allied Education, 2012)
It is a matter of time when it is either completelywithdrawn or its present shape goes under transformation much under budgetarypressure rather than the WTO obligations. The subsidy withdrawal will have manyramifications. It will impact GDP both on supply and demand side besidesdenting farmer’s purchasing power and food security in terms of physicalavailability. This paper will analyze the effect of subsidy withdrawal andexperience of a few countries about subsidy elimination on the basis ofselected studies.